Rancang Bangun Mesin Pengisi Bantal Sebagai Alat Bantu Produktivitas UMKM - Syahdila Darama; Rizal Hanifi; Reza Reza (Peneliti.net, 2023)
The economy in Indonesia is very diverse, there are many things that can help the community’s economy. One of them is from the industrial sector which plays a role in supporting the national community’s economy to design simple and affordable tools for MSMEs through this final project. Nationally, UMKM have an important role in improving the nation’s economy because they are labor-intensive businesses that require a lot of labor. The micro, small, medium enterprises UMKM group involves many business groups as a reinforcement in avoiding the economic crisis. Residents in Indonesia definitely use pillows for comfort in a comfortable sleep and can improve the quality of stable sleep to carry out daily activities. The solution to this problem is to make innovative updates so that they are not monotonous. Manual human resources cause a lot of time and production is less rapid and requires machines to speed up and save energy. Design and build this simple pillow filling machine that can be operated directly by the general public who can produce one pillow with a size of 60 cm x 50 cm with a time of 2.31 minutes/pillow and can get 200 pillows/day, 1.200 pillows/week, 5.200 pillows/month, 62.400 pillows/year with normal work 8 hours of work. The need for dakron silicon materials for production needs so that the budget plan issued is managed which is 66.66 kg/day, 400 kg/week, 1.733 quintals/month, and 20.800 quintals/year.